KAPITALISME, PROFESIONALISME DOSEN, DAN PERAN PEMERINTAH PADA PENDIDIKAN TINGGI - Asmoni, Asmoni (Reflektika, 2019)
The purpose of this paper is to examine the dynamics of higher education in the flow of capitalism. After conducting a library study, the following are some indicators in education in the USA. In educational capitalism, there is a need for government contributions in terms of funding as is done in several countries that adhere to capitalism, including the USA. On the other hand, it is also necessary to pay attention to satisfaction in higher education, measured by customer satisfaction. The performance and quality of lecturers is the focus. Variables that are important are individual variables, psychological variables, and organizational variables.